A comparative study on clinical features and outcomes of acute pancreatitis between diabetic and non-diabetic hospitalized patients (BIRDEM Medical Journal, 2020)
Background: Pancreatitis is a serious disorder of pancreas. This study was designed to investigate the clinical features and outcomes of the hospitalized patients with acute pancreatitis (AP) with or without diabetic mellitus (DM).Methods: A total of 90 adult hospitalized patients with AP diagnosed in three different tertiary hospitals were evaluated for inclusion in prospective study on clinical, laboratory and outcome parameters. After exclusion according to exclusion criteria, 68 patients were enrolled finally, and out of 68 patients 34 were diabetic with AP from BIRDEM and 34 AP patients were non-diabetic from Dhaka Medical College and BSMMU.Results: The major clinical features, laboratory markers were significantly (p